2004
DOI: 10.1080/00288233.2004.9513603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of differentNeotyphodiumendophytes on root distribution of a perennial ryegrass(Lolium perenneL.) cultivar

Abstract: Plants of perennial ryegrass either endophyte-free or infected with Neotyphodium lolii endophyte strain AR1, AR37 or wild-type, were grown in 105-mm-diameter tubes of sand in a glasshouse. Root angles were determined by counting root intercepts on semi-circular stainless steel mesh transects running from near the edge of the tube at the sand surface to directly under the plant. The average number of root intercepts did not vary between endophyte strains or between their average and the endophyte-free treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…This suggests that tiller size/density compensation processes (Matthew et al 1996) were being expressed and, as reported by Matthew et al (1991), the results for root counts were not confounded by plant type)defoliation effects. Other work (Crush et al 2004) suggests that any differences in endophyte strains among the ryegrasses would have only very minor effects on root distribution. The two-weekly root counts would have been sufficiently frequent to minimise errors associated with root death and decay between successive samplings (Gibbs & Reid 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that tiller size/density compensation processes (Matthew et al 1996) were being expressed and, as reported by Matthew et al (1991), the results for root counts were not confounded by plant type)defoliation effects. Other work (Crush et al 2004) suggests that any differences in endophyte strains among the ryegrasses would have only very minor effects on root distribution. The two-weekly root counts would have been sufficiently frequent to minimise errors associated with root death and decay between successive samplings (Gibbs & Reid 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In some circumstances endophyte infection has been shown to increase root/shoot DW ratios in ryegrass (Hesse et al 2005;Ren et al 2007), but there have been few investigations of endophyte effects on root system shape. In a previous experiment (Crush et al 2004), endophyte infection in perennial ryegrass decreased root mean GSA so that there were fewer roots close to the surface than in endophyte-free plants, but different endophyte strains had little effect on root distribution. Another experiment, however, showed no effect of endophyte infection on ryegrass root distribution (Popay & Crush 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Results suggest that endophyte-mediated responses to water deficit are a combination of drought avoidance, tolerance and recovery mechanisms, and may vary among individual symbionts in the population. Alterations of root architecture [176][177][178], and morphology and functions [144,179,180] may be the primary basis for drought tolerance in endophyte-infected grasses. Protection of growth meristems and cell membrane functions by antioxidants from oxidative stress caused by excess of free radicals may be a secondary mechanism [27,89,168].…”
Section: Mechanisms Of Endophyte-induced Tolerance To Abiotic Stressesmentioning
confidence: 99%